Production of bioethanol by direct bioconversion of oil-palm industrial effluent in a stirred-tank bioreactor - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Hussin, S. Nahdatul I. S. (Springer Science, 2009)
The purpose of this study was to evaluate the feasibility of producing bioethanol from palm-oil mill effluent generated by the oil-palm industries through direct bioconversion process. The bioethanol production was carried out through the treatment of compatible mixed cultures such as Thrichoderma harzianum, Phanerochaete chrysosporium, Mucor hiemalis, and yeast, Saccharomyces cerevisiae. Simultaneous inoculation of T. harzianum and S. cerevisiae was found to be the mixed culture that yielded the highest ethanol production (4% v/v or 31.6 g/l). Statistical optimization was carried out to determine the operating conditions of the stirred-tank bioreactor for maximum bioethanol production by a two-level fractional factorial design with a single central point. The factors involved were oxygen saturation level (pO2%), temperature, and pH. A polynomial regression model was developed using the experimental data including the linear,quadratic, and interaction effects. Statistical analysis showed that the maximum ethanol production of 4.6% (v/v) or 36.3 g/l was achieved at a temperature of 32C, pH of 6, and pO2 of 30%. The results of the model validation test under the developed optimum process conditions indicated that the maximum production was increased from 4.6% (v/v) to 6.5% (v/v) or 51.3 g/l with 89.1% chemicaloxygen-demand removal.